Laurence Binyon poet, scholar of East and West - Hatcher, John 1940- (Clarendon Press, 1995)
Binyon is best remembered today for his 1914 Great War elegy 'For the Fallen', carved on countless war graves and recited annually at Remembrance Sunday services, but his importance extends well beyond this one famous poem. In fact, Binyon was a poet, dramatist, translator, art historian, and critic, whose influence in a wide range of fields is only now beginning to be recognized. During his forty-year career at the British Museum, he built a world reputation as a pioneering scholar and interpreter of Eastern art, one of the first to challenge the West's myopic assumption that it held a monopoly on beauty and truth. Revealing the subtle continuities between the poet and East West mediator, this fascinating study of his life and work restores Binyon to his rightful place in British cultural history, as one of the most benign and quietly influential voices of the early twentieth century